2017
DOI: 10.1007/s10103-017-2395-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effect of root surface modification with citric acid, EDTA, and aPDT on adhesion and proliferation of human gingival fibroblasts and osteoblasts: an in vitro study

Abstract: Root demineralization is used in Periodontics as an adjuvant for mechanical treatment. The aim of this study was to evaluate the effects of root surface modification with mechanic, chemical, and photodynamic treatments on adhesion and proliferation of human gingival fibroblasts and osteoblasts. Root fragments were treated by scaling and root planing (C-control group), EDTA (pH 7), citric acid plus tetracycline (CA-pH 1), and antimicrobial photodynamic therapy (aPDT) with toluidine blue O and red laser (pH 4). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 40 publications
0
5
0
2
Order By: Relevance
“…34 This chemical treatment has an effect similar to that of air-powder abrasive systems for the removal of endotoxins produced by bacteria on hydroxyapatite-coated implants. 15 Additionally, despite its high acid concentration and low pH, this acid does not reduce cell viability, 36 even on titanium surfaces. 37 Therefore, we assume that citric acid is able to remove biofilms related to peri-implant diseases without affecting the periodontal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…34 This chemical treatment has an effect similar to that of air-powder abrasive systems for the removal of endotoxins produced by bacteria on hydroxyapatite-coated implants. 15 Additionally, despite its high acid concentration and low pH, this acid does not reduce cell viability, 36 even on titanium surfaces. 37 Therefore, we assume that citric acid is able to remove biofilms related to peri-implant diseases without affecting the periodontal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The idea of adding the aPDT group to the present study arose from the results of previous studies. 9,12 Pessoa et al 21 in their case report demonstrated that the use of 10 mg/mL TBO caused clinical signs of enamel demineralization and symptoms of hypersensitivity. But later, Damante et al 12 demonstrated that 100 μg/mL TBO caused a significant loss of dentin microhardness and surface wear of 9.06 ± 7.69 μm and could be as effective as citric acid conditioning to stimulate cell adhesion and proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…2,4 Root surface alterations caused by periodontal disease can impair wound healing by connective tissue formation or periodontal regeneration. 9 Root conditioning agents such as citric acid, 10 high-power lasers, 11 and aPDT have been applied to improve periodontal tissue attachment to the root surfaces. 12 The principles of aPDT involve the use of a nontoxic light-sensitive dye called a "photosensitizer" (PS) combined with irradiation of a harmless visible light (low energy).…”
Section: Introductionmentioning
confidence: 99%
“…A possibilidade de biomodificação radicular por corantes de terapia fotodinâmica foi descrita apenas por estudos de nosso grupo de pesquisa (DAMANTE et al, 2013;PESSOA et al, 2015;BARROS et al, 2016;DAMANTE et al 2016;KARAM et al,2013, FERREIRA et al, 2018DAMANTE et al, 2019).…”
Section: Apdt Como Biomodificador Radicularunclassified
“…Estes sinais e sintomas foram atribuídos a uma desmineralização ácida provocada pelo azul de toluidina durante o tratamento (PESSOA et al, 2015). Outros estudos, usando o azul de toluidina O em concentrações diferentes (100 µg / ml em água deionizada), também encontraram uma faixa de pH levemente ácido (4 a 5) para este fotossensibilizador (DAMANTE et al, 2016;KARAM et al, 2017;FERREIRA et al, 2018). Quanto maior a pré-irradiação tempo, maior é o efeito de desmineralização (DAMANTE et al, 2016).…”
Section: )unclassified